Feasibility of an Interprofessional, Simulation-Based Curriculum to Improve Teamwork Skills, Clinical Skills, and Knowledge of Undergraduate Medical and Nursing Students in Uganda - Santorino, Data; Dubé, Mirette M.; Bajunirwe, Francis; Kyakwera, Catherine; Robinson, Traci; Najjuma, Josephine N.; Cherop, Moses; Abesiga, Lenard; Namata, Tamara; Brenner, Jennifer L.; Singhal, Nalini; Twine, Margaret; et al. (Simulation in Healthcare, 2021)
Introduction: Many deaths in Sub-Saharan Africa are preventable with provision of skilled healthcare. Unfortunately, skills decay after training. We determined the feasibility of implementing an interprofessional (IP) simulation-based educational curriculum in Uganda and evaluated the possible impact of this curriculum on teamwork, clinical skills (CSs), and knowledge among undergraduate medical and nursing students. Methods: We conducted a prospective cohort study over 10 months. Students were divided into 4 cohorts based on clinical rotations and exposed to rotation-specific simulation scenarios at baseline, 1 month, and 10 months. We measured clinical teamwork scores (CTSs) at baseline and 10 months; CSs at baseline and 10 months, and knowledge scores (KSs) at baseline, 1 month, and 10 months. We used paired t tests to compare mean CTSs and KSs, as well as Wilcoxon rank sum test to compare group CS scores. Results: One hundred five students (21 teams) participated in standardized simulation scenarios. We successfully implemented the IP, simulation-based curriculum. Teamwork skills improved from baseline to 10 months when participants were exposed to: (a) similar scenario to baseline {baseline mean CTS = 55.9% [standard deviation (SD) = 14.4]; 10-month mean CTS = 88.6%; SD = 8.5, P = 0.001}, and (b) a different scenario to baseline [baseline mean CTS = 55.9% (SD = 14.4); 10-month CTS = 77.8% (SD = 20.1), P = 0.01]. All scenario-specific CS scores showed no improvement at 10 months compared with baseline. Knowledge was retained in all scenarios at 10 months. Conclusions: An IP, simulation-based undergraduate curriculum is feasible to implement in a low-resource setting and may contribute to gains in knowledge and teamwork skills. (Sim Healthcare 00:00–00, 2020)
A Cohort Study
Keywords: Interprofessional simulation; Teamwork; Clinical skills; Uganda; Africa